Irrigation, Salinity, and Rural Communities in Australia's Murray-Darling Basin, 1945–2020 - Rothenburg, Daniel (Palgrave Studies in World Environmental History, 2023)
XVIII, 303 p. 11 illus., 10 illus. in color.